Implementasi Reading Aloud dengan Dukungan Media PowerPoint dalam Pembelajaran Maharah Qira’ah - Mujahida, Anni; Windarsih, Ayu (Mahira: Journal of Arabic Studies & Teaching, 2026)
The teaching of Arabic reading skills still faces challenges, particularly students’ difficulties in accurately reading Arabic texts in terms of pronunciation, intonation, and comprehension. Previous research has generally been dominated by conventional approaches, and few studies have integrated the reading aloud method with PowerPoint, particularly in the context of MTs. This study aims to describe the implementation of the PowerPoint-based reading aloud method in maharah qira’ah instruction at MTs Negeri 10 Sleman. This study employs a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. The results indicate that the application of the PowerPoint-based reading aloud method effectively enhances students’ qira’ah skills, particularly in pronunciation and text comprehension, while also boosting their confidence in reading aloud. PowerPoint serves as a visual aid that facilitates vocabulary and context comprehension, although challenges include time constraints and low self-confidence among some students. The implications of this study suggest that integrating the reading aloud method with PowerPoint is an effective instructional innovation for improving students’ qira’ah skills and self-confidence.